Independent Educational Organization Effective Methods (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article talks about the importance of the organization of independent education for students' learning, methods and stages of its organization. Positive and negative features of independent education are revealed and concluded at the end.